First detection of human T-Iymphotropic virus in blood donors in Benin shows that testing is required to improve blood safety... - Amoussa, Adjile Edjide Roukiyath; Kashima, Simone; Djobessi, Didier; Barreto, Fernanda Khouri; Davou, Denise; BIGOT, KOFFI ANDRÉ; ANANI, LUDOVIC YAOVI; Lourenço, Jose; Giovanetti, Marta; Sabino, Ester; RAHIMY, MOHAMED CHÉRIF DEEN; Alcantara, Luiz Carlos Junior (My University, 2018)
Introduction Human T-Iymphotropic virus (HTLV) is a blood-borne infection that can be transmitted via blood transfusion. Knowing that blood safety can improve blood transfusion to prevent dissemination of viral infections in medical facilities, there is no routine pre-transfusion screening for HTLV in ail blood banks in the Republic of Benin. This study aims to estimate the prevalence of HTLV infection in blood donors and describes the characteristics of positive donors. Methods A HTLV prevalence study was carried out by screening 2,035 samples by an enzyme-linked immunoassay obtained from six blood banks located throughout the Republic of Benin. The PCR method was used to conflrm and type ail the ELISA reactive samples. Results and discussion Twelve subjects, ail volunteer blood donors, were found with positive serology confirmed by a specifie HTLV type 1 PCR assay, representing an overall seroprevalence of 0·59%. Furthermore, seven subjects were indeterminate for anti-HUV-l/2 antibody and only one sample was confIrmed positive for HTLV type 1 in a PCR reaction. These are the flfSt cases of HUV detection among blood donors in Benin Republic, whose blood was already transfused to recipients. This result emphasizes that HUV needs to be considered as a Public Health issue in the Republic of Benin. Conclusion This study reports positive result of HUV infection among blood donors in the blood banks of Benin Republic in West Africa and highlights the inclusion of screening tests and strategies to reduce its transmission.
Keywords: Blood donors; HTLV; HTLV prevalence; HUV testing.